2022
DOI: 10.1039/d2se00849a
|View full text |Cite
|
Sign up to set email alerts
|

BaTb0.3Fe0.7O3−δ: a new proton-conductor-derived cathode for proton-conducting solid oxide fuel cells

Abstract: BaTbO3 is a much less focused proton-conductor than the traditional BaCeO3-BaZrO3 system due to its lower proton conductivity. However, the present study reveals that using BaTbO3 as the parent material...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…† The excellent match demonstrated the good reliability of the DCT model. Compared with the common method of a single characteristic time (1 − exp(t/s)), 53 which is normally applied for dense samples whose transport process is limited by surface exchange, the DCT model gave much better results, i.e., an improved matching with the experimental data and a reduced standard deviation, Fig. S6.…”
Section: Electrical Conductivity Relaxationmentioning
confidence: 99%
“…† The excellent match demonstrated the good reliability of the DCT model. Compared with the common method of a single characteristic time (1 − exp(t/s)), 53 which is normally applied for dense samples whose transport process is limited by surface exchange, the DCT model gave much better results, i.e., an improved matching with the experimental data and a reduced standard deviation, Fig. S6.…”
Section: Electrical Conductivity Relaxationmentioning
confidence: 99%
“…It should be mentioned that the performance of the BCF cell is superior to the performance of the BSCF cell in this study and also larger than most of the H-SOFCs reported in Refs. [11,17,[45][46][47][48][49][50][51][52][53][54][55][56][57][58]. The chemical compatibility examination between BCF and BZY is carried out, and the result is shown in Fig.…”
Section: (B) To Further Explore Thementioning
confidence: 99%